Herbal smoking products: a systematic content analysis and mapping of the e-retail market. Issue 4 (9th February 2021) - Gupta, Arpit; Sharda, Shweta; Yogitha, Pothamsetty; Goel, Sonu; Goyal, Ashima; Gauba, Krishan
Abstract : Objective: To assess the online availability and e-marketing strategies of herbal smoking products (HSPs). Methodology: Google, Yahoo and Bing were searched using relevant keywords related to HSPs. The first 50 records were retrieved and duplicates were removed. Two trained and calibrated authors screened the records according to the eligibility criteria and extracted data from each selected retail-webpage as per the pre-tested data extraction form. Results: Out of the initial 1044 records obtained, 73 retail webpages were finally included. Most of the webpages about HSPs hailed from India followed by the USA. The results showed 24 brands with about 189 flavour variants that are readily available online to all age groups including minors, with price per pack (20 sticks) of herbal cigarettes ranging from INR (₹) 51 to 1830 (median 588). There are no regulations regarding the sale and marketing of HSPs concerning age restrictions and display of health warnings. Conclusion: HSPs are readily available online at affordable prices and attractive variants for customers of all ages. The flavour appeal and the health benefit appeal is being used to target minors and young women. There is an urgent need for some regulations on the sale and e-marketing of such products that have an enormous potential to be used as a gateway to tobacco smoking.